2022
DOI: 10.1155/2022/2103151
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Biochemical Potential of Moroccan Onions (Allium cepa L.)

Abstract: Allium cepa L. remains the most cultivated Allium species in Morocco and around the world. With the purpose of making the first biochemical characterization of Moroccan onions, several biochemical components have been measured in eleven onion ecotypes. Onions were collected as seeds from different geographical origins and cultivated in the same environment, to eliminate the influence of the environment on biochemical expression. Moisture, total phenols, flavonoids, antioxidant activity, total and reducing suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The slow-release N from CaCN 2 could contribute to amino acid formation, vital for flavonoid synthesis [40]. It is worth noting that the flavonoid content reported in this study was notably in the same range reported by Amal et al [60], whose findings indicated 0.67 mg CE g −1 in white onions.…”
Section: Effect Of N Source Fertilizer On Onion Bulb Flavonoidssupporting
confidence: 87%
“…The slow-release N from CaCN 2 could contribute to amino acid formation, vital for flavonoid synthesis [40]. It is worth noting that the flavonoid content reported in this study was notably in the same range reported by Amal et al [60], whose findings indicated 0.67 mg CE g −1 in white onions.…”
Section: Effect Of N Source Fertilizer On Onion Bulb Flavonoidssupporting
confidence: 87%
“…The worth of an attribute was evaluated using the OneR classifier at the following parameters: seed for the cross-validation, 1; the number of folds for the cross-validation, 10; the minimum number of objects in a bucket, 6; using the training data to evaluate attributes rather than cross-validation, False. Ten attributes were selected to maintain the ratio of attributes (10) to the number of cases (100) of 1:10. Then, the discriminative models were developed based on selected data using a 10-fold cross-validation mode.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of red onion, including, e.g., the content of flavonols, anthocyanins, total phenols, sulfur dioxide, and reducing sugars, can differ depending on, among others, the cultivar, line, and ecotype [7][8][9][10]. Therefore, distinguishing different onion types may be important.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, the domestic demand is attained through importation [5]. In the year 2022, the Philippines Statistics Authority (PSA), reported that 12.45% of the onion supply comes from importation [6]. Yellow onions are one of the most grown onion varieties in the country.…”
Section: Introductionmentioning
confidence: 99%